Numerical and analytical evaluation of the compressive performance of Steel Tube (ST)-reinforced Concrete Filled Stainless Steel Tubular (CFSST) columns - Md. Imran Kabir; Munim Shahriar Rehan; Zarif Ahmed; Ann Nazmun Sakib; Muntasir Mohammad Shoeb (Results in Engineering)
Utilizing numerical and analytical methods, this paper assesses compressive performance of Steel Tube (ST)-reinforced Concrete Filled Stainless Steel Tube (CFSST) columns under axial compression. Considering both geometric and material nonlinearities, Finite Element (FE) model was developed and validated against test results. The validated FE model was then employed to carry out an extended parametric study covering a wide range of parameters which includes the width of the outer tube, diameter of the inner tube, thickness of the tubes, material strengths and heights of the columns. The study results indicated that the axial strengths of the columns could be increased by up to 36 % and 30 % for short and long columns, respectively considering an optimized combination of parameters. Besides, notable enhancements in the ductility and toughness of the columns were observed, with ductility experiencing a 10–40 % increase and toughness improving by up to 57 %. Furthermore, the FE predicted axial strengths of the columns were compared with those calculated from different design codes, such as ACI 318–14, EC 4, ANSI/AISC 360–16, and AS 2327. Existing design codes underestimated the peak axial strengths of the columns, particularly for long columns. Hence, a modified squash strength formula was proposed where a good alignment with the FE predicted strengths was observed, with a mean predicted-to-test strength ratio of 0.99 and 1.1 for stub and long columns, respectively. The outcomes of this study thus provided valuable insights regarding the compressive performance of the ST-CFSST columns, and thus emphasize their potential applicability in modern construction.